Critical Characteristics of Housing and Housing Supports for Individuals with Concurrent Traumatic Brain Injury and Mental Health and/or Substance Use Challenges: A Qualitative Study - Maria Jennifer Estrella (MDPI AG, 2021)
Traumatic brain injury (TBI) and mental health and/or substance use challenges (MHSU) are commonly co-occurring and prevalent in individuals experiencing homelessness; however, evidence suggests that systems of care are siloed and organized around clinical diagnoses. Research is needed to understand how housing and housing supports are provided to this complex and understudied group in the context of siloed service systems. This study aimed to describe critical characteristics of housing and housing supports for individuals with concurrent TBI and MHSU from the perspectives of service users with TBI and MHSU and housing service providers. Using basic qualitative description, in-depth interviews were conducted with 16 service users and 15 service providers. Data were analyzed using thematic analysis techniques. Themes capture core processes in finding and maintaining housing and the critical housing supports that enabled them: (1) overcoming structural barriers through service coordination, education and awareness raising, and partnerships and collaborations; and (2) enabling engagement in meaningful activity and social connection through creating opportunities, training and skills development, and design of home and neighborhood environments. Implications for practice, including the urgent need for formalized TBI and MHSU education, support for service providers, and potential interventions to further enable core housing processes are discussed.